2015
DOI: 10.1016/j.radonc.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of vaginal dilator use adherence and efficacy following radiotherapy

Abstract: Background and purpose Vaginal stenosis (VS) after pelvic radiotherapy can impair long-term quality of life. We prospectively assessed adherence and efficacy of VD use as the primary and secondary objectives, respectively. Material and methods Women with gastrointestinal (n=63) and gynecologic (n=46) cancers self-reported use and VD size in monthly diaries for 12 months after radiotherapy. Adherence was measured as actual VD use out of recommended times over 12 months (3×/week × 52 weeks = 156). Results Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 25 publications
1
49
0
4
Order By: Relevance
“…However, observational data indicate that regular use of dilator following RT is associated with lower rates of self-reported VS 3436. Further clinical trials are ideally needed; however, the difficulties of designing appropriate trials to establish a causal relationship are widely acknowledged 1,22.…”
Section: Prevention Strategies and Outcomesmentioning
confidence: 99%
“…However, observational data indicate that regular use of dilator following RT is associated with lower rates of self-reported VS 3436. Further clinical trials are ideally needed; however, the difficulties of designing appropriate trials to establish a causal relationship are widely acknowledged 1,22.…”
Section: Prevention Strategies and Outcomesmentioning
confidence: 99%
“…Bahng et al reported that patient use of a vaginal dilator significantly reduces incidence of vaginal atrophy [71]. In a prospective study of vaginal dilator adherence, continued use of a vaginal dilator 6 months after pelvic radiotherapy decreased the rate of vaginal stenosis [79]. Patients with higher mean vaginal doses may benefit the most from use of a vaginal dilator [80].…”
Section: Toxicitymentioning
confidence: 99%
“…The study admits that observational studies suggest that regular vaginal dilation may improve rates of patient-reported vaginal stenosis [81]. Low rates of adherence to use of a vaginal dilator result in difficulty interpreting data on this topic however [71,79,80]. The use of a vaginal dilator following VBT may be a controversial topic, but many investigators, including the authors recommend routine use for patients that are not sexually active.…”
Section: Toxicitymentioning
confidence: 99%
“…Research into the acceptability and efficacy of vaginal dilation, as a prophylactic or as a treatment for vaginal stenosis, has yielded inconsistent results (Bakker et al, 2014;Law et al, 2015;Miles & Johnson, 2014) and adherence to vaginal dilation protocols tends to be poor (Huffman et al, 2016;Law et al, 2015;Miles & Johnson, 2014). Little evidence exists within the literature to support the use of vaginal dilation during active RT, when inflammatory activity and psychological strain is in a more acute phase (Bakker et al, 2014;Johnson, Miles, & Cornes, 2010;Miles & Johnson, 2014).…”
Section: Vaginal Dilationmentioning
confidence: 99%